Diversifikasi Aktivitas Ibu Rumah Tangga Nelayan di Pulau Kecil (Faculty of Social Science, Universitas Negeri Semarang, 2019)
This research was conducted to provide an overview of the economic dynamic of the community, especially housewives in small island in an effort to fulfill livelihood. This study it might be able to provide information that can be used to solve the problems of livelihood of fishing communities in small island. This study uses ethnographic approach. The data collected is secondary and primary data. The interview, discussion, and observation occur more when the researcher is involved in the activity or when the informant is making, or selling the cake, it is not uncommon for an interview to occur while eating lunch, dinner and breakfast. Based on the verification of work, there are economic activities of housewives are ula-ula, making snacks, kiosk, wickerwork and saving. This activity was carried out so that they could increase the livelihood of the household. These activities depend on each other. Snack depends on the results of ula-ula, keeping the stall also done if there is not ula-ula activity, as well as plait the mat.